IMPLEMENTASI KEPERAWATAN KOMPLEMENTER BEKAM PADA PENDERITA HIPERTENSI DI DESA CURAH KALONG KECAMATAN BANGSALSARI KABUPATEN JEMBER - Purnama, Yugi Hari Chandra; Lailil Fatkuriyah (LPPM Universitas dr. Soebandi, 2023)
Hypertension is a non-communicable disease that is currently on the rise and is a disease of the blood vessels. Treatment of hypertension can be done pharmacologically or non-pharmacologically. The purpose of this community service is to introduce and implement it in the community in Curah Kalong Village, especially for people with hypertension. This community service activity includes the preparation, process, and evaluation stages. Participants were divided into three groups: people with hypertension, people with a history of hypertension, and the general public. This activity was carried out on March 2–3 2019 until it was finished at the Curah Kalong Village Hall, Bangsalsari District, Jember. Based on the results, there were 49 peoples who attended, with around 67% women (32 people) and the remaining 33% men (17 people). The results show that giving cupping complementary nursing therapy (average) can reduce systolic and diastolic blood pressure in hypertensive patients. The people of Curah kalong Village are enthusiastic about the socialization and implementation of cupping complementary nursing so that the benefits can be felt directly